Lexical Variation Used by Muslim Speech Community in Saren Jawa: A Sociolinguistic Study - I Komang Widiasmara; I Nyoman Adi Jaya Putra; Ni Luh Putu Sri Adnyani (Journey: Journal of English Language and Pedagogy, 2023)
Language variations emerge the production of new lexicons regularly. Lexical variations can be found in ethnic places since the community stands with their strong culture and tradition. Saren Jawa is a Muslim village in the middle of Hinduism majority. This village has language phenomenon where the Muslim speech community tends to use Balinese to interact each other. This study aimed to analyse the lexical variations used by Muslim speech community in Saren Jawa. This study applied sociolinguistic study with natural approach in form of qualitative research. The study focused on five language domains namely, family, neighbourhood, friendship, school, and religion. In collecting the data, participatory and non-participatory observation were used in five language domains. The lexical variations were compared by using Swadesh list and categorized into their types. The result found a number of 108 lexical differences out of 207 standard lexicons compared to Swadesh. Neighbourhood domain committed the most lexical variations, while the fewest obtained by the school and religion domains. There were four types of lexical variations categorized in this study, including semasiological, onomasiological, formal and contextual variations. Therefore, the Muslim speech community in Saren Jawa still maintains their language as how they communicate among Balinese area